Effectiveness of Motivational Therapy on Enhancing Self-esteem, to maintain Absti-nence among Alcohol Dependent Patients in Sri Sai Foundation psychiatric hospital, Tamaka, Kolar. - Ramya M; Jairakini Aruna; Rajesh R (Journal of Clinical and Biomedical Sciences)
Background:Motivational therapy is very important among alcohol dependent patients to increase the self-esteem to bring the changes in the level of confidence, positive health, problem solving abilities, maintaining abstinence from the alcohol.1 Hence the researcher felt the need to improve the self-esteem level of alcohol dependent patients to maintain abstinence from alcohol in selected de-addiction centres, kolar. Objective: To find out the effectiveness of motivational therapy on enhancing self-esteem to maintain absti-nence among alcohol dependent patients. Materials and Methods: An evaluative approach with Pre experimental one group pre-test, post-test design was adopted. Rosenberg self-esteem scale was used to collect the data. The main study was conducted at Sri Sai Foundation and Life Care Centre Kolar with the sample size of 80 alcohol dependent patients, by using Non- probability, convenient sampling technique and the collected data were analyzed and interpreted by using de-scriptive and inferential statistics. Results: The findings of the study revealed that 100% (80) of alcohol dependent patients had low self-esteem level before Motivational therapy. Whereas after Motivational therapy 100% (80) of the alcohol dependent pa-tients had reached to normal self-esteem level. Further study revealed that after Motivational therapy mean scores of self-esteem level i.e 18.75 with SD of 2.14 was higher than before Motivational therapy mean score i.e 9.51with SD of 1.58 .The obtained t value 32.2 was greater than the table value (1.960) at 0.05 level of signifi-cance which indicates that Motivational therapy was effective on enhancing self-esteem levels of alcohol de-pendent patients. Conclusion: The self-esteem level of alcohol dependent patients was low before Motivational therapy whereas after Motivational therapy all the patients had reached to normal self-esteem level. Hence Motivational therapy is effective in improving self-esteem level of alcohol dependent patients. Key words- Effectiveness, Motivational therapy, Self-esteem, Abstinence, Alcohol Dependent patients